Inflammation-Related Changes in Mood Disorders and the Immunomodulatory Role of Lithium - Kosma Sakrajda (International Journal of Molecular Sciences, 2021)
Mood disorders are chronic, recurrent diseases characterized by changes in mood and emotions. The most common are major depressive disorder (MDD) and bipolar disorder (BD). Molecular biology studies have indicated an involvement of the immune system in the pathogenesis of mood disorders, and showed their correlation with altered levels of inflammatory markers and energy metabolism. Previous reports, including meta-analyses, also suggested the role of microglia activation in the M1 polarized macrophages, reflecting the pro-inflammatory phenotype. Lithium is an effective mood stabilizer used to treat both manic and depressive episodes in bipolar disorder, and as an augmentation of the antidepressant treatment of depression with a multidimensional mode of action. This review aims to summarize the molecular studies regarding inflammation, microglia activation and energy metabolism changes in mood disorders. We also aimed to outline the impact of lithium on these changes and discuss its immunomodulatory effect in mood disorders.